How do police officers talk about their encounters with ‘the public’? Group interaction, procedural justice and officer constructions of policing identities - Radburn, Matthew (Criminology & criminal justice, 2022)
Despite widespread empirical support for Procedural Justice Theory, understanding the role of police psychology in shaping encounters with ‘citizens’ is relatively opaque. This article seeks to address this gap in the literature by exploring how officers talk about themselves and their colleagues and deploy social categories to understand their interactions with ‘the public’. The qualitative thematic analysis draws upon 22 semi-structured interviews conducted with officers in various roles and teams within a large metropolitan police force in England. Our thematic analysis demonstrates the centrality of procedural fairness in officers’ talk (in terms of internal relations with colleagues and external relations with ‘the public’). Interviewees described complex internalised theories of social relations, differentially positioning themselves in relation to other colleagues and multiple ‘publics’ often depicted along socioeconomic and geographical lines. Officers described their interactions with ‘the public’ in sequential and historical terms with complex and changing (often intergroup) power dynamics. Implications of the analysis for understanding the role of social identity processes among police officers and how this underlying conceptualisation might shape police–‘citizen’ encounters are discussed.